Molecular Alterations of PI3K/Akt/mTOR Pathway: A Therapeutic Target in Endometrial Cancer. (12th January 2014) - Pavlidou, Athanasia; Vlahos, Nikos F.
Abstract : It is well established that the PI3K/Akt/mTOR pathway plays a central role in cell growth and proliferation. It has also been suggested that its deregulation is associated with cancer. Genetic alterations, involving components of this pathway, are often encountered in endometrial cancers. Understanding and identifying the rate-limiting steps of this pathway would be crucial for the development of novel therapies against endometrial cancer. This paper reviews alterations in the PI3K/Akt pathway, which could possibly contribute to the development of endometrial cancer. In addition, potential therapeutic targets of this pathway with emphasis on the mTOR inhibitors are also presented.